(untitled) (Interdisciplinary Studies Journal, 2024)
This article evaluates the potentialities of Peer Instruction (PI) in higher education for both face-to-face and online classes, while examining application strategies, impacts on student participation and comprehension, and the difficulties educators encounter when integrating this methodology into their pedagogical practices. Grounded principally in the studies of Ferreira and Kempner-Moreira (2017), Cavaignac, Gouveia and Reis (2020), and Pinto et al. (2012), through a bibliographic review, the analysis explores various dimensions of this pair-centered process. The findings indicate how PI fosters skills such as critical thinking, leadership, and communication, while also highlighting the need for ongoing teacher training and adaptation to digital resources. The study demonstrates that this proposal encourages interaction and collaboration among students, strengthening engagement and active learning. In addition, it underscores the relevance of Information and Communication Technologies (ICTs) in applying this dynamic, showing how these tools may enhance pedagogical practice. It is recommended that future research examine, in greater depth, strategies for adopting PI supported by ICTs, especially in online classes, as well as carry out comparative analyses across different cultural and institutional contexts to identify successful practices for implementing this methodology in diverse educational settings.